ANALISIS KEBUTUHAN PEMBELAJARANPENDIDIKAN AGAMA ISLAM - Murtafiah, Siti; Tasun, Muhammad; Zaitun, Zaitun; Khairiah, Siti; Tasun, Muhamad (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
Islamic Religious Education (IRE) plays a crucial role in shaping the character, religious attitudes, and morality of students amid the tide of modernization. However, its implementation often faces real challenges such as the diversity of student characteristics, monotonous teaching methods, and digital disruption. This research is urgently needed because without a comprehensive needs analysis, PAI instructional design risks losing relevance to the realities of today’s generation. This article aims to analyze PAI learning needs from the perspectives of students, the curriculum, teacher competencies, and the learning environment. The method used is a literature review analyzing various scientific sources, journal articles, and relevant policy documents. The research results indicate that PAI needs analysis must encompass three main dimensions: First, the integration of interactive digital technology and gamification to accommodate the characteristics of Generation Z and Alpha. Second, the reconstruction of the curriculum and methods oriented toward a contextual approach so that religious material can be implemented in daily life. Third, strengthening teachers’ pedagogical and digital competencies to consistently internalize the values of religious moderation in order to counter radicalism. This structured analysis has proven to be a strategic foundation for improving the quality and effectiveness of learning. A recommendation for future research is to conduct an empirical field study using a Research and Development (R&D) approach to develop Islamic Education (PAI) learning modules or materials based on actual needs at specific educational institutions.